Analysis of junior high school students’ critical thinking skills in solving HOTS questions viewed from learning style - Mustakim, Siti Salina; Dewi, Aulia Rahma; Sa’dijah, Cholis; Rofiki, Imam (Universitas Negeri Malang, Indonesia, 2024)
Currently, junior high school students' critical thinking abilities are relatively low. To address this, one effective approach is through the use of HOTS (Higher Order Thinking Skills) questions. However, students' abilities to solve HOTS questions often vary due to differences in learning styles. While this study emphasizes the relationship between learning styles and critical thinking, it does not include a gender-specific analysis or a comprehensive exploration of HOTS questions across all levels of Bloom's taxonomy. This research analyzes junior high school students' critical thinking abilities in solving HOTS questions regarding learning style. The descriptive research used a qualitative approach. Data collection techniques were carried out by distributing questionnaires, tests with HOTS question instruments covering Bloom's C4 to C6 levels, and interviews. The interactive analysis model uses data collection, condensation, display, and conclusion drawing/verification. The research results show that students with a visual learning style tend to write answers completely and systematically, can identify problems in a structured manner, and have high accuracy, so they often recheck students' answers. Students with an auditory learning style have difficulty writing complete and structured answers but have good storytelling skills and often explain answers verbally even though they do not write them in detail. Kinesthetic students tend to write answer